English Teachers’ Perceptions of Changes to GCSE Assessment - Grace, Harry (2016)
England’s education system under the current Conservative Government is undergoing some monumental changes, specifically to the GCSE qualifications. Among these reforms are significant changes to how students are assessed, with methods of assessment such as coursework retired and replaced with end-of-course exams. The literature review of this paper highlights some of the problems for teachers and students that the reforms are causing and contributing to and also highlights a huge discrepancy between research literature and the aims of the reforms. A qualitative approach was taken to explore English teacher’s perceptions of the recent changes to assessment, utilizing interviews to gauge opinion. The findings suggest that teachers are generally not supportive of the changes and call for use varied types of assessment to examine students. The key recommendations resulting from this study are a suggested wider exploration of the topic in order to support the conclusions made and to help raise awareness of some of the side-effects of the reforms so that perhaps the adverse effects can be addressed.